PENGEMBANGAN MODEL MATERI AJAR MATEMATIKA DAN IPA BERBASIS BAHASA INGGRIS DENGAN PEMANFAATAN ARTIFICIAL INTELLIGENCE - Rosyid, Abdul; Halira V., R. Lungguh; Hidayati, Istiqlaliah Nurul; Ginanjar, M. (LPPM Universitas Islam 45 Bekasi, 2025)
This Community Service activity aimed to develop bilingual Mathematics and Science teaching materials using Artificial Intelligence (AI) technology. The target participants were Mathematics and Science teachers at SMP Kesatuan Bogor. The program was conducted throughout February 2026, employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). It began with a focus group discussion to identify relevant topics to be redesigned in English. Teachers were then trained on how to utilize AI tools such as ChatGPT, DeepSeek, and Gamma to create contextual and level-appropriate materials. The outcome included two Mathematics and three Science learning modules written in English, enriched with problem-solving exercises in the form of case studies. Evaluation results indicated that the teachers were able to independently develop bilingual teaching materials, and students showed a high level of engagement with the content. This activity had a positive impact on enhancing teachers’ capacity to design innovative lessons and provided students with a more interactive and meaningful learning experience.